The Effect of Motor Vehicle Tax Bleaching Program on Taxpayer's Behavior through the Mediation of Tax Paying Intention in Lampung Province - Erin, Erin; Balliyand, Ahmad Faiz Zindan; Murtanto, Murtanto; Faisal, Aris Riantori (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Taxes are an instrument of state revenue so that various government efforts are made to increase taxpayer participation, one of which is through the tax whitening program. This study aims to analyze the effect of the tax whitening program organized by the Government of Lampung Province on the behavior of taxpayers either directly or through mediation of intention to pay taxes. The research subjects were determined by purposive sampling technique in order to obtain a sample of 65 taxpayers. Data analysis was carried out using the Partial Least Square method through the SmartPLS version 3.0 program. The results of the analysis show that: (1) the tax whitening program has a positive and significant effect on the intention to pay taxes, (2) the tax whitening program has a positive and significant effect on the behavior of taxpayers, (3) the intention to pay taxes has a positive and significant effect on the behavior of taxpayers (4) the intention to pay taxes can play a role in mediating the tax whitening program on the behavior of taxpayers.